2010
DOI: 10.1163/22941932-90000004
|View full text |Cite
|
Sign up to set email alerts
|

Wood Anatomical features and chemical composition of Prosopis kuntzei from the paraguayan chaco

Abstract: Anatomical features for Prosopis kuntzei Harms were studied by light and scanning electron microscopy. The wood is mainly diffuse-porous with indistinct growth ring boundaries. Vessel diameter ranges between 11 to 193 μm. The thick-walled fibres average 1275 μm in length. Parenchyma bands are 66 to 1066 μm apart. Heartwood extractives were studied in the vessels, rays and part of the fibres by means of scanning UV microspectrophotometry. The pyrolitic lignin content is 30.7%. The percentage of polyphenolic com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
1
3
0
3
Order By: Relevance
“…The relationship of these peaks with polysaccharides has been reported in the literatüre. 33,45,57,[61][62][63] These peak values showed a decrease in the control samples after the weathering testing, a result which is compatible with the literature. Yildiz et al 64 in their study found that in parallel with the increase in the UV exposure time, these peaks decreased in coniferous wood species, while they increased in leafy wood species.…”
Section: Surface Composition Of Wood After Natural Weatheringsupporting
confidence: 92%
See 1 more Smart Citation
“…The relationship of these peaks with polysaccharides has been reported in the literatüre. 33,45,57,[61][62][63] These peak values showed a decrease in the control samples after the weathering testing, a result which is compatible with the literature. Yildiz et al 64 in their study found that in parallel with the increase in the UV exposure time, these peaks decreased in coniferous wood species, while they increased in leafy wood species.…”
Section: Surface Composition Of Wood After Natural Weatheringsupporting
confidence: 92%
“…The C–H found in cellulose, cellulose, hemicelluloses and the CO and cellulose present in lignin express the C–O bonds in hemicelluloses. The relationship of these peaks with polysaccharides has been reported in the literatüre . These peak values showed a decrease in the control samples after the weathering testing, a result which is compatible with the literature.…”
Section: Resultsmentioning
confidence: 91%
“…Prosopis kuntzei Harms. P. kuntzei wurde bereits anatomisch, chemisch und technologisch untersucht (Giménez et al 1997;Scholz et al 2005Scholz et al , 2010 und gilt aufgrund seiner Inhaltsstoffe als dauerhaft (Tortorelli 1956;Dimitri et al 2000;Giménez und Moglia 2003;Scholz et al 2010). Nach Salvat et al (2004) weisen in Methanol gelöste Inhaltsstoffe der Rinde antibakterielle Wirksamkeit auf.…”
Section: Introductionunclassified
“…VorbetrachtungGérardin et al (2004) schreiben die Dauerhaftigkeit von P. africana neben bioziden Extraktstoffen auch hydropho-ben Gumen zu, da die zur Substratbesiedelung notwendige Feuchte fehlt. Das Vorkommen solcher Gumen kann auch für die untersuchte Holzart nicht ausgeschlossen werden(Scholz et al 2010). In diesem Zusammenhang empfehlenJunga und Militz (2005) u.a.…”
unclassified
See 1 more Smart Citation